Development of a bead-based Luminex assay using lipopolysaccharide specific monoclonal antibodies to detect biological threats from Brucella species - Silbereisen, Angelika (BMC Microbiol, 2015)
BACKGROUND: Brucella, a Gram-negative bacterium, is classified as a potential bioterrorism agent mainly due to the low dose needed to cause infection and the ability to transmit the bacteria via aerosols. Goats/sheep, cattle, pigs, dogs, sheep and rodents are infected by B. melitensis, B. abortus, B. suis, B. canis, B. ovis and B. neotomae, respectively, the six classical Brucella species. Most human cases are caused by B. melitensis and B. abortus. Our aim was to specifically detect Brucellae with ‘smooth’ lipopolysaccharide (LPS) using a highly sensitive monoclonal antibody (mAb) based immunological assay. METHODS: To complement molecular detection systems for potential bioterror agents, as required by international biodefense regulations, sets of mAbs were generated by B cell hybridoma technology and used to develop immunological assays. The combination of mAbs most suitable for an antigen capture assay format was identified and an immunoassay using the Luminex xMAP technology was developed. RESULTS: MAbs specific for the LPS O-antigen of Brucella spp. were generated by immunising mice with inactivated B. melitensis or B. abortus cells. Most mAbs recognised both B. melitensis and B. abortus and antigen binding was not impeded by inactivation of the bacterial cells by γ irradiation, formalin or heat treatment, a step required to analyse the samples immunologically under biosafety level two conditions. The Luminex assay recognised all tested Brucella species with ‘smooth’ LPS with detection limits of 2 × 10(2) to 8 × 10(4) cells per mL, depending on the species tested. Milk samples spiked with Brucella spp. cells were identified successfully using the Luminex assay. In addition, the bead-based immunoassay was integrated into a multiplex format, allowing for simultaneous, rapid and specific detection of Brucella spp., Bacillus anthracis, Francisella tularensis and Yersinia pestis within a single sample. CONCLUSION: Overall, the robust Luminex assay should allow detection of Brucella spp. in both natural outbreak and bio-threat situations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-015-0534-1) contains supplementary material, which is available to authorized users.